PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN (Studi Empiris pada Perusahaan Jasa non Keuangan yang terdaftar di Bursa Efek Indonesia Tahun 2009-2011) - Prastya Puji Lestari; Nur Cahyonowati (Diponegoro Journal of Accounting, 2013)
The purpose of this study is to empirically examine the effect of good corporate governance to corporate performance. Corporate governance is measured by Tobin’s Q. Corporate governance are measured by proportion of independent board, managerial ownership, institutional ownership, foreign ownership, the independence of the audit committee, and the quality of audit, with firm size as a control variable. Sample on this study is non-financial services selected by using purposive sampling method. There are 111 non-financial service companies fulfilling criterions. The method of data anaysis is used a multiple regression analysis. The results of this research indicates that institutional ownership variable, independence of audit committee, quality of audit, and firm size have significant influence on firm performance. Meanwhile, independence of commisaris variable, manajerial ownership, and foreign ownership has no significant influence on firm performance (Tobin’s Q).